Integrated project of food chain in the protected area of Pollino - Contò, Francesco; La Sala, Piermichele; Papapietro, Paolo (Economics of Agriculture, 2010)
The introduction of the Integrated Projects of Food Chain requires the development of models capable of interpreting the dynamics of vertical and horizontal coordination between agents and the definition of the issues that mostly affect the ability of professionals to provide added value to goods and products and to acquire a competitive advantage in exchange. With reference to setting up Local Production System of the Pollino - Lagonegrese, characterized by the development of an "atypical" food chain, for which the main factor of integration and competitive advantage lies in the strong link between companies and territory and in the social and economic value of the agriculture of protected area, this work focuses on the importance of the natural resources to the development of the food chain in the mountain region.